AN ANALYSIS OF TEACHING LEARNING PROCESS - Salwa Chaira (English Education Department, 2016)
This article is about an analysis of teaching and learning process in an English classroom. it also gives an explanation of the presence of Input-Interaction-Output (IIO). In the article, there are details of the type of input and role applied by the teacher, the type and role of interaction built, and the type of output and its lead. Besides, other elements such as English talk and lesson explanation, the feedback given by the teacher, language view, materials, and activity in the classroom, etc will include in the essay. The method applied in the article is document analysis. The result is that the way the teacher teaches, the method she applies, and the approach she implements can offer and encourage them to obtain the knowledge in a good way. These factors seem agreeable as the students can perceive her teaching style well. However, the material or the subject provided by the teacher seems much lower for the students’ capacity. Thus, the writer suggests that Monique offer a little bit higher input.